Turno de trabalho, privação de sono e insatisfação da imagem corporal em mulheres trabalhadoras de um frigorífico do sul do Brasil - Leite, Heloísa Marquardt (Universidade do Vale do Rio dos Sinos, 2016)
Objectives: Shift-working women may have metabolic, psychological and behavioral changes, as well as a greater predisposition to body image dissatisfaction. The aim of this study was to investigate the association between shift work and sleep duration with body image dissatisfaction among women shift workers in southern Brazil. Methods: Cross-sectional study with shift-working women between 18 and 60 years old. The outcome, body image dissatisfaction, was assessed using the Stunkard Figure Rating Scale. Information of shift work, sleep duration and other explanatory variables were collected through a questionnaire. For the exposure, an aggregated variable, termed “sleep deprivation”, was created combining the two main exposures (shift work and sleep duration), being the exposure category night-shift workers who slept <7h/day. The respective values of prevalence ratios (PR) and 95% confidence intervals (95% CI) were estimated using Poisson regression with robust variance. Results: A total of 505 women with a mean age (standard deviation) of 33.7 (± 8.6) years were evaluated. The prevalence of body image dissatisfaction among the shift-working women was 42.4% (95% CIs: 38.0 to 48.7) and 93.0% of these wished they had a smaller body size. After adjusting for potential confounding factors, shift-working women with “sleep deprivation” exhibited a probability 28% higher (PR = 1.28; 95% CIs: 1.04 to 1.58; p = 0.022) of body image dissatisfaction than those without “sleep deprivation” Conclusion: The results of this study indicates a relevance of “sleep deprivation” (night shift and <7 hours of sleep/day) in relation to affective aspects of body image on shift-working women. It is recognized that body image disorders are associated with weight control actions. Thus, proper knowledge of body image disorders and its possible risk factors can orientate health promotion strategies in specific and vulnerable populations.
Keywords: imagem corporal; Trabalho em turnos; Sono; Mulheres; Body imagem; Shift work; Sleep; Women; ACCNPQ::Ciências da Saúde::Saúde Coletiva